Dr. H.G. Shastri felicitation volume - Śāstrī, Hariprasāda Gaṅgāśaṅkara, 1919-; Parikh, P. C.; Shelat, Bharati Kirtikumar; Parmar, Thomas (H.G. Shastri Felicitation Volume Committee, 1994)
Festschrift in honor of 75th birth anniversary of Hariprasāda Gaṅgāśaṅkara Śāstrī, b. 1919; comprises articles on Indian civilization and Sanskrit literature.